Pengaruh Kepemimpinan Transformasional Terhadap Motivasi Kerja - Kadir Kadir; Wini Sariningsih (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2018)
Leadership with a new approach is needed to deal with changes very quickly both from insideor from outside of the organization. Leadership with this new approach is transformative leadership that is able to develop initiatives, be able to empower staff and organizations into a change a way of thinking, developing a vision, understanding organizational goals and bringing about sustainable improvements. This study aims to prove that the transformational leadership style is able to bring changes that have an impact on increasing the motivation of subordinates to achieve performance as expected, and also to determine the extent the influence of each dimension of transformational leadership on employee work motivation. The study was conducted the government employee in one of the Bandung local government agencies using a sampling technique of 74 respondents. The independent variables in this study consisted of charismatic, inspirational, intellectual stimulation and individual attention while the dependent variable was work motivation. The results showed that transformational leadership simultaneously had a significant effect with a coefficient of determination of 63.8%. In order to increase the influence of transformational leadership, it is recommended that the leaders must have to pay more attention in placement of employees accordance with their educational background and expertise and do not forget the importance of delegating authority and responsibilities in a straightforward and clear manner to make room for employee creativity.